2019
DOI: 10.1071/mf18490
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal by tropical floodplain wetlands through denitrification

Abstract: Excess nitrogen (N) leading to the eutrophication of water and impacts on ecosystems is a serious environmental challenge. Wetlands can remove significant amounts of N from the water, primarily through the process of denitrification. Most of our knowledge on wetland denitrification is from temperate climates; studies in natural tropical wetlands are very scarce. We measured denitrification rates during a dry and a wet season in five floodplain forests dominated by Melaleuca spp., a coastal freshwater wetland o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The hotspots were identified by multiplying the denitrification potential for wetlands within each sub-catchment (D t ; mg m −2 h −1 ), by the area of wetlands that were flooded during the day. Total denitrification was predicted from the NO − 3 concentration of the floodwater, which is a major driver of denitrification for similar wetlands in the region (Adame et al, 2019b, this study, Figure 3) and other tropical and temperate wetlands (Piña-Ochoa and Álvarez-Cobelas, 2006). The NO − 3 concentrations were obtained from the Source Catchment model and corroborated by direct measurements obtained by the Water Quality Monitoring Program of the Great Barrier Reef (Euramo station at Tully River; Orr et al, 2014).…”
Section: Nitrogen Fate and Transportmentioning
confidence: 90%
See 4 more Smart Citations
“…The hotspots were identified by multiplying the denitrification potential for wetlands within each sub-catchment (D t ; mg m −2 h −1 ), by the area of wetlands that were flooded during the day. Total denitrification was predicted from the NO − 3 concentration of the floodwater, which is a major driver of denitrification for similar wetlands in the region (Adame et al, 2019b, this study, Figure 3) and other tropical and temperate wetlands (Piña-Ochoa and Álvarez-Cobelas, 2006). The NO − 3 concentrations were obtained from the Source Catchment model and corroborated by direct measurements obtained by the Water Quality Monitoring Program of the Great Barrier Reef (Euramo station at Tully River; Orr et al, 2014).…”
Section: Nitrogen Fate and Transportmentioning
confidence: 90%
“…We measured denitrification rates at eight sites representative of coastal wetlands of these catchments. Previous studies have shown no significant differences in denitrification potential between the dry and wet seasons (Adame et al, 2019b). Thus, all measurements were conducted once at each site at the end of the wet season (May to June) in either 2017 or 2018.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations